2019
DOI: 10.3390/pharmaceutics11020075
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Quantity of Exhaled Aerosols Released into the Environment during Nebulisation

Abstract: Background: Secondary inhalation of medical aerosols is a significant occupational hazard in both clinical and homecare settings. Exposure to fugitive emissions generated during aerosol therapy increases the risk of the unnecessary inhalation of medication, as well as toxic side effects. Methods: This study examines fugitively-emitted aerosol emissions when nebulising albuterol sulphate, as a tracer aerosol, using two commercially available nebulisers in combination with an open or valved facemask or using a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 31 publications
4
56
2
1
Order By: Relevance
“…The size of the aerosol and flow are determined by the exit diameter of the aperture holes [35]. Previous research showed that the residual mass remaining in a VMN was independent of the patient interface, heating and humidification settings [26,28]. As the same VMN was used for each scenario, the aerosol generation rate should be consistent across all scenarios with changes in inhaled dose and fugitive emissions influenced by the patient interface, the gas-flow rate and the breathing profiles.…”
Section: Discussionmentioning
confidence: 99%
“…The size of the aerosol and flow are determined by the exit diameter of the aperture holes [35]. Previous research showed that the residual mass remaining in a VMN was independent of the patient interface, heating and humidification settings [26,28]. As the same VMN was used for each scenario, the aerosol generation rate should be consistent across all scenarios with changes in inhaled dose and fugitive emissions influenced by the patient interface, the gas-flow rate and the breathing profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory infectious diseases can be transmitted via three routes, namely contact, airborne and fomite [27]. Similarly, a higher risk of infection is associated with close proximity to the source patient and decrease rapidly with the distance [28][29][30][31][32][33]. With the same initial concentration, a larger quantity of mass released may be expected to experience a slower dilution [34,35].…”
Section: Graphical Abstractmentioning
confidence: 99%
“…With the same initial concentration, a larger quantity of mass released may be expected to experience a slower dilution [34,35]. Due to the initial velocity, the exhaled gas and particles can travel in the air over a distance which is determined by the ventilation airflow, gravity force related to particle diameters and buoyancy forces of thermal J o u r n a l P r e -p r o o f bodies [16,17,26,31,33,[36][37][38]. Larger particles (>50μm) may settle on wall surfaces or floors quickly because the significance of gravity is greater than ventilation.…”
Section: Graphical Abstractmentioning
confidence: 99%
See 2 more Smart Citations